Managed Entry Agreements for Oncology Drugs: Lessons from the European Experience to Inform the Future - Pauwels, Kim; Huys, Isabelle; Vogler, Sabine; Casteels, Minne; Simoens, Steven (Frontiers in Pharmacology, 2017)
Objectives: The aim of this study is to conduct an analysis on the regulation and application of managed entry agreements (MEA) for oncology drugs across different European countries. Methods: Literature search and document analysis were performed between September 2015 and June 2016 to collect information on the regulatory framework and practice of MEA in Belgium, The Netherlands, Scotland, England & Wales, Sweden, Italy, Czech Republic and France. An overview of the content and typology of MEA applied for oncology drugs between 2008 and 2015 was generated based on publically available sources and contributions by national health authorities. Semi-structured interviews were conducted with representatives of national health authorities involved in the management or negotiation of MEA. Results: The application of MEA differs across countries and across different indications for the same drug. Financial based agreements are prevailing due to their simplicity compared to performance-based agreements. Performance-based agreements are less commonly applied in the European countries except for Italy. In the Netherlands, application of performance-based agreements was stopped due to their inability to deal with dynamics in the market, which is highly relevant for oncology drugs. Conclusions: MEA constitute a common policy tool that public payers in European countries use to ensure early access to high priced oncology drugs. In light of strengths and weakness observed for managed entry agreements and the expected developments in the oncology area, the importance of MEA is likely to grow in the future.